Retraction of ‘Chemical composition of the essential oil extracted from the leaves of the dwarfish (Chamaerops humilis L.) palm tree of Morocco (Region of Benslimane)' (Journal of Applied Pharmaceutical Science, 2015)
Article titled ‘Chemical composition of the essential oil extracted from the leaves of the dwarfish (Chamaerops humilis L.) palm tree of Morocco (Region of Benslimane) published in Journal of Applied Pharmaceutical Science, volume: 3, issue: 8, August, 2013 (Saïd et al., 2013)’ has been retracted, due to some conflict amongst the authors in relation to the results of the study.Thus, we retract this article from the literature according to the guidelines of Committee on Publication Ethics (Wager et al., 2009).